PENGARUH TOTAL ASSETS TURN OVER, CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON ASSETS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 – 2018 - Erlina Novy Indriani; Untung Sriwidodo; Suprihatmi Sri Wardiningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The population in this research is all pharmaceutical companies listed on the Indonesia Stock Exchange year 2015 - 2018. Sampling techniques by using the purposive sampling technique obtained as much as 7 out of 10 companies. Data analysis methods using classic assumptions, multiple linear regression analyses, t tests, F tests, and coefficient of determination (R2). The results of T-Test analysis show that profitability has significant effect on the company's value because it has a significance value, total assets turn over significantly affect the value of the company because it has a significance value of, current ratio significantly affects the value of the company because it has a significance value, debt to equity ratio has significant effect on the company's value as it has a significance value. The F test results show that total assets turn over, current ratio, debt to equity ratio, and return on assets have significant effect on the company's value because of the significance value.